1998
DOI: 10.1089/hum.1998.9.16-2385
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Herpes Simplex Virus Thymidine Kinase/Ganciclovir Bystander Effect and Its Antitumor Efficacy In Vivo by Pharmacologic Manipulation of Gap Junctions

Abstract: Apigenin, a flavinoid, and lovastatin, an HMG-CoA reductase inhibitor, upregulated gap junction (GJ) function and dye transfer in tumors expressing GJ and were inactive in the GJ-negative tumor line N2a. N2a cells transfected with the connexin 43 gene showed restored cell-to-cell dye transfer, which could then be improved nearly fourfold by addition of apigenin. To test the drugs in HSV thymidine kinase/ganciclovir (HSV-tk/GCV) tumor killing, mixtures of 90% wild-type (WT) with 10% HSV-tk gene-modified MCA38 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…A bystander effect, meaning HSV-TK non-expressing cells near the HSV-TK expressing cells can also be killed, is mainly responsible for a dramatic tumor ablation or regression by HSV-TK/GCV treatment in animal studies. 7,8,[16][17][18] However, clinical trials for glioma using this treatment have failed. [19][20][21][22] One of the major reasons may be due to the delivery manner of HSV-TK into glioma cells located only in the direct vicinity of the injection site, but fail to transduce infiltrating tumor cells or distant tumor areas that eventually serve as the reservoirs for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bystander effect, meaning HSV-TK non-expressing cells near the HSV-TK expressing cells can also be killed, is mainly responsible for a dramatic tumor ablation or regression by HSV-TK/GCV treatment in animal studies. 7,8,[16][17][18] However, clinical trials for glioma using this treatment have failed. [19][20][21][22] One of the major reasons may be due to the delivery manner of HSV-TK into glioma cells located only in the direct vicinity of the injection site, but fail to transduce infiltrating tumor cells or distant tumor areas that eventually serve as the reservoirs for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Owing to the loss of gap junction among C6 glioma cells, it is speculated that the second mechanism may have a major role in which, to a great extent, death of the neighboring C6 cells is induced by their uptake of cytotoxic GCV triphosphate released from BMSC-TK cells after GCV treatment. As transfection of Cx43 gene into C6 cells can restore gap junction, 27,28 cytotoxic phosphorylated GCV can be transported between C6 cells through gap junction, in addition to the uptake of phosphorylated GCV through apoptotic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Therefore, pharmacological strategies aiming at upregulating the level of connexins have been proposed in order to increase the BE. [30][31][32][33][34][35] The delivery of connexin genes together with TK has also been evaluated, and it has been shown that the BE could be induced in gap junction deficient cancer cells. 26,36 A very different type of BE that is independent of the level of connexins has been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…44 However, this may be cell typespecific. [45][46][47][48] It is not clear whether this is effective in the cells examined in this study. This suggests that continuous treatment or a combination with other agents is required for the full regression of tumor growth, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%